Dinamika Ketahanan Pondok Pesantren Waria Al-Fatah Yogyakarta 2006-2018 M: The Dynamics of Resilience of Al-Fatah Yogyakarta "Waria" (Transexual) Islamic Boarding School 2006-2018 AD - Yazid, Achmad (Journal of Islamic History, 2022)
Al-Fatah Waria Islamic Boarding School is a place for Yogyakarta transgender people to get closer to God Almighty. This Transgender Islamic Boarding School was once just a kind of transgender association for small-scale recitations. It started with an earthquake that rocked Yogyakarta, where a member of the waria died in an earthquake, from which the waria held a recitation or sent a prayer to their friends who died. In its establishment, there are unique dynamics, ranging from moving from place to place, or often getting threats from internal and external. This article focuses on the ins and outs of the ups and downs of Islamic boarding school survival, as well as the triggers for the survival of this Transgender Islamic Boarding School which increasingly exists in the times. This article belongs to the type of history, which uses historical research methods. The stages in the historical research method, among others, namely. Heuristics or source collection, which consists of primary and secondary sources, both in written and oral form in the form of interviews. Verification or source criticism, both internal and external criticism. Interpretation or interpretation of sources, as well. Historiography or historical writing. The results of this study are, the origin of the birth of the Transgender Islamic Boarding School, starting from one transgender person named Mother Maryani who attended the recitation at the residence of K. H. Hamrolie. After many years, Mother Maryani then gathered transgender people throughout Yogyakarta to be invited to recite the Koran. After carrying out the special recitation for transgender people, K. H. Hamrolie proposed to build a special Islamic boarding school for transgender women, named Pesantren Waria Monday-Thursday, located at Notoyu and the residence of Mrs. Maryani. In addition, in its growth and development, there were two conflicts, namely internal conflicts, and external conflicts with the Islamic organization FJI, so that this pesantren was difficult to become big. As for the existence of this pesantren, there is encouragement from within the pesantren itself, such as the family community, as well as from outside parties such as academics and the Legal Aid Institute. Meanwhile, the obstacles to the progress of the pesantren are the frequent changing locations, members or students who do not stay, and the frequent threats from outside.